Factor Analysis Related to Self Efficacy Obesity Management in Students Faculty of Nursing Science - Dwi Riniasih; Nyimas Heny Purwati; Fitrian Rayasari (Jurnal Keperawatan, 2022)
Obesity management will give optimal results, if the person does diet, physical activity, and behavior therapy seriously. Therefore, a strong self-efficacy is needed to get maximum results. This study aims to analyze the factors related to obesity management self-efficacy in students of the Faculty of Nursing, University of Muhammadiyah Jakarta. This study used a large probability sampling. a sample of 83 students.This research uses the methodanalytical descriptivewith cross-sectional design. Data was collected by means of interviews, surveys and distributing questionnaires. The data analysis technique used was logistic regression (logistic regression). This study shows the results of a obtained that Attitude with P value: 0.001 (< 0.05), Physical and Emotional Conditions with P value: 0.001 (< 0.05), and Gender with P value: 0.032 (< 0.05) hasconnectionwhich is significant to the Self Efficacy of Obesity Management Students of the Faculty of Nursing, University of Muhammadiyah Jakarta. Efforts to increase obesity management self-efficacy are byimprove body condition, decrease stress and readiness to go on a diet. This study recommends the need for to be used as a reference material, providing information and understanding to students about factors related to obesity self-efficacy.